Analisa Tinggi Gelombang dan Periode Gelombang di Pelabuhan Laut Niaga Brondong Kecamatan Brondong Kabupaten Lamongan - Iwan Wahyudijanto (KERN, 2020)
Brondong Harbor is a small port as a fishermen port located in Brondong sub-district, Lamongan Regency. The wave height at the port pool greatly influences the loading and unloading at the port. In this study a wave height prediction analysis study was conducted at the port. The height of the waves can be predicted from several other factors: Fetch length, length of wind gust and wind speed. These waves are waves caused by wind. Besides that other factors that influence are fetch width, water depth, basic roughness and stability of the atmosphere